Self-Medication Practices in Remote, Border, and Island Areas: A Literature Review - Tya Palpera Utami; Najmah Najmah; Haerawati Haerawati (Indonesian Journal of Global Health Research, 2025)
Health is defined as a state of physical, mental, and social well-being that enables every individual to lead a socially and economically productive life. One of the initial efforts in treatment is the practice of self-medication. Self-medication is the independent use of medication without supervision or direct consultation with a health professional, with the aim of addressing health complaints experienced. The purpose of this study was to examine the description and risk factors of self-medication in Indonesia and globally. This research method is a descriptive observational study using a literature review design, with the following databases: Wiley Online Library, PubMed, and ScienceDirect From 2021 to 2025, a total of 25 articles were reviewed. The search strategy for articles in Wiley Online Library, PubMed, Google Scholar, and ScienceDirect used four keywords: "Self-medication"; "Drugs"; "Remote Areas"; and Risk Factors." Search results that met the criteria were then subjected to article analysis. Self-medication is common in various parts of the world, especially in areas with limited access to healthcare. This practice is increasingly prevalent in Indonesia, particularly in remote areas such as border and coastal areas. These areas face numerous challenges, including difficult-to-reach locations, limited healthcare facilities, and a shortage of medical personnel. These conditions encourage people to self-medicate without the supervision of healthcare professionals. This self-medication practice carries significant potential risks, such as inappropriate medication use, which can lead to increased drug resistance and other health problems. Therefore, it is crucial to understand the factors influencing self-medication in remote areas to effectively mitigate its negative effects.